Postmodern approaches to the short story - Iftekharuddin, Farhat (Contributions to the study of world literature, 2003)
Postmodernism, as a mode of the contemporary short story, has been clearly established and recognized by short story theorists. But postmodern theory, as pervasive as it has become among academics in the last half century, has scarcely been applied to the short story genre in particular. Many contemporary scholars, nonetheless, are currently making use of certain postmodern thematic approaches to help them determine meanings of particular short stories. T.